2014
DOI: 10.1111/cas.12502
|View full text |Cite
|
Sign up to set email alerts
|

PD‐1 expression on peripheral blood T‐cell subsets correlates with prognosis in non‐small cell lung cancer

Abstract: PD-1 expression in peripheral blood T-cells has been reported in several kinds of cancers, including lung cancer. However, the relationship between PD-1 expression in peripheral blood T-cells and prognosis after treatment with a cancer vaccine has not been reported. To elucidate this relationship, we analyzed PD-1 expression in the peripheral blood T-cells of patients with non-small cell lung cancer. The blood samples used in this study were obtained from patients enrolled in phase II clinical trials of a pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
51
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 36 publications
6
51
2
Order By: Relevance
“…Overall survival rates are significantly lower in patients with high B7-H1 expression compared with those with low B7-H1 expression in some tumors (14)(15)(16)(17). Abundant PD-1 on tumor-infiltrating T cells is also associated with poor overall survival (6,18,19). Thus, research on B7-H1-PD-1 interactions in the tumor microenvironment is now focused on a new target for immunotherapy in patients with various types of cancer who show high B7-H1 expression on tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…Overall survival rates are significantly lower in patients with high B7-H1 expression compared with those with low B7-H1 expression in some tumors (14)(15)(16)(17). Abundant PD-1 on tumor-infiltrating T cells is also associated with poor overall survival (6,18,19). Thus, research on B7-H1-PD-1 interactions in the tumor microenvironment is now focused on a new target for immunotherapy in patients with various types of cancer who show high B7-H1 expression on tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…Boosting for peptide‐specific IgG responses, which were clearly detectable in all 21 patients, was especially apparent in 63% or 100% of patients after the 1st cycle or 2nd cycle of vaccination, respectively. We have reported that boosting of IgG responses is well correlated with overall survival …”
Section: Discussionmentioning
confidence: 98%
“…PD-1 is expressed in tumor samples and has prognostic value in cancer patients 2426. Moreover, PD-1 expression in peripheral blood cells increased with tumor stage and correlated with prognosis in various cancer 25,27,28. Thus, we believe that PD-1 expression coupled to medical imaging could impact the way to perform diagnosis and prognosis and to predict therapy outcome in cancer.…”
Section: Introductionmentioning
confidence: 93%